Investigating unmet need for healthcare using the European Health Interview Survey: a cross-sectional survey study of Luxembourg - Maria Ruiz-Castell; Jessica Barré; Valerie Moran; Marc Suhrcke; Laetitia Huiart (BMJ Open)
Objectives We investigate the prevalence of unmet need arising from wait times, distance/transportation and financial affordability using the European Health Interview Survey. We explore associations between individual characteristics and the probability of reporting unmet need.Design Cross-sectional survey conducted between February and December 2014.Setting and participants 4004 members of the resident population in private households registered with the health insurance fund in Luxembourg aged 15 years and over.Outcome measures Six binary variables that measured unmet need arising from wait time, distance/transportation and affordability of medical, dental and mental healthcare and prescribed medicines among those who reported a need for care.Results The most common barrier to access arose from wait times (32%) and the least common from distance/transportation (4%). Dental care (12%) was most often reported as unaffordable, followed by prescribed medicines (6%), medical (5%) and mental health (5%) care. Respondents who reported bad/very bad health were associated with a higher risk of unmet need compared with those with good/very good health (wait: OR 2.41, 95% CI 1.53 to 3.80, distance/transportation: OR 7.12, 95% CI 2.91 to 17.44, afford medical care: OR 5.35, 95% CI 2.39 to 11.95, afford dental care: OR 3.26, 95% CI 1.86 to 5.71, afford prescribed medicines: OR 2.22, 95% CI 1.04 to 4.71, afford mental healthcare: OR 3.58, 95% CI 1.25 to 10.30). Income between the fourth and fifth quintiles was associated with a lower risk of unmet need for dental care (OR 0.29, 95% CI 0.16 to 0.53), prescribed medicines (OR 0.38, 95% CI 0.17 to 0.82) and mental healthcare (OR 0.17, 95% CI 0.05 to 0.61) compared with income between the first and second quintiles.Conclusions Recent and planned reforms to address waiting times and financial barriers to accessing healthcare may help to address unmet need. In addition, policy-makers should consider additional policies targeted at high-risk groups with poor health and low incomes.